1986
DOI: 10.1139/z86-092
|View full text |Cite
|
Sign up to set email alerts
|

The influence of insects on the distribution, microhabitat choice, and behaviour of the Burwash caribou herd

Abstract: This study examined the influence of insects (mosquitoes and oestrids) on the distribution, microhabitat choice, and behavior of a population of mountain caribou. The study was conducted in the Burwash area of southwestern Yukon Territory during the summers of 1982 and 1983. Mosquito density, the presence or absence of oestrids, and the distribution, microhabitat use, and insect-avoidance behavior of the caribou were observed. Seasonal activity budgets for caribou were calculated. Mosquitoes became active in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 15 publications
1
110
1
Order By: Relevance
“…14: 227-233 perature, biting insects, snow depth, and availability of cover (Edge et al, 1985;Downes et al, 1986;Sweanor & Sandegren, 1989;Kilpatrick et al, 2001). According to Irwin & Peek (1983), social relation¬ ships and population density played a secondary role to food availability in the range size of elk in Montana.…”
Section: Rangifer Special Issue No 14 2003mentioning
confidence: 99%
“…14: 227-233 perature, biting insects, snow depth, and availability of cover (Edge et al, 1985;Downes et al, 1986;Sweanor & Sandegren, 1989;Kilpatrick et al, 2001). According to Irwin & Peek (1983), social relation¬ ships and population density played a secondary role to food availability in the range size of elk in Montana.…”
Section: Rangifer Special Issue No 14 2003mentioning
confidence: 99%
“…However, the majority of the study areas (>75 %) consisted of vegetation types, where no or very small difference in decay rate between vegetation types can be assumed (Skarin, submitted ). Other studies have shown that reindeer as well as other ungulates seek insect avoidance at high altitudes and at wind-exposed sites (Downes et al, 1986; Table 2. Included independent variables in the candidate RUF regressions models for each survey method (faecal standing crop (FSC) and faecal accumulation rate (FAR)) and area, number of parameters (k), the coefficient of determination (R 2 ), difference among AIC c scores (AIC c Δ), and AIC c weights (w), only the models with AIC c Δ < 2 are shown (Burnham & Anderson, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…It is known that Rangifer avoid predators (Rettie & Messier, 2000) and select forage quantity (Mårell et al, 2002) at large spatial scales, and select patches with forage of high nutritive quality at finer scales (Johnson et al, 2001;Mårell et al, 2002). Other known limiting factors for reindeer and caribou in the snow-free season are harassment from insects such as oestrid flies and mosquitoes (Downes et al, 1986;Hagemoen & Reimers, 2002;Colman et al, 2003). Thus, at the larger spatial scales there should be a selection against areas with high levels of insect harassment.…”
Section: Introductionmentioning
confidence: 99%
“…Culley et al, 1991;Day & Edman, 1984b;Downes et al, 1986;Edman et al, 1972Edman et al, , 1985Edman & Scott, 1987;Kale et al, 1972;Klowden, 1983;Klowden & Lea, 1979;Molyneux & Jefferies, 1986;Scott et al, 1988Scott et al, , 1990Walker & Edman, 1985a. Host-defensive reactions and other aspects of host location are reviewed by Edman & Spielman (1988).…”
Section: General Considerationsmentioning
confidence: 99%
“…There are several references to biting insects, including mosquitoes, causing animals to seasonally migrate away from areas of intense biting. Downes et al (1986) review the effects of insects, including mosquitoes, on caribou. Those interested in the protective measures adopted by animals against biting flies should also read the paper by Waage (1981) on how the zebra got its stripes, and his earlier paper (1979) on the evolution on insect-vertebrate associationsalthough mosquitoes are not referred to in either publication.…”
Section: General Considerationsmentioning
confidence: 99%